Reliability of shear wave elastography for the assessment of gastrocnemius fascia elasticity in healthy individual - Jiping Zhou; Yuyi Lin; Jiehong Zhang; Xingxian Si’tu; Ji Wang; Weiyi Pan; Yulong Wang (Scientific Reports, 2022)
Abstract The mechanical properties of the deep fascia, particularly their stiffness, strongly affect the development of muscle pathologies (such as compartment syndrome) and the action of the muscles. However, the mechanical characteristics of the deep muscular fascia are still not clearly understood. The present study focuses on examining the reliability of ultrasonic shear wave elastography (USWE) devices in quantifying the shear modulus of the gastrocnemius fascia in healthy individuals, particularly their ability to measure the shear modulus of the deep fascia of the gastrocnemius during ankle dorsiflexion. Twenty-one healthy males (age: 21.48 ± 1.17 years) participated in the study. Using USWE, the shear moduli of the medial gastrocnemius fascia (MGF) and lateral gastrocnemius fascia (LGF) were quantified at different angles during passive lengthening. The two operators took turns measuring each subject’s MGF and LGF over a 1-h period, and operator B took an additional measurement 2 h later. For the intra-operator test, the same subjects were measured again at the same time of day 5 days later. Both the intrarater [intraclass correlation coefficient (ICC) = 0.846–0.965)] and interrater (ICC = 0.877–0.961) reliability values for measuring the shear moduli of the MGF and LGF were rated as excellent; the standard error of the mean (SEM) was 3.49 kPa, and the minimal detectable change (MDC) was 9.68 kPa. Regardless of the ankle angle, the shear moduli of the LGF were significantly greater than that of the MGF (p < 0.001). Significant increases in the shear moduli of both the MGF and the LGF were observed in the neutral position compared to the relaxed position. These results indicate that USWE is a reliable technique to assess the shear modulus of the gastrocnemius fascia and detect its dynamic changes during ankle dorsiflexion. USWE can be used for biomechanical studies and intervention experiments concerning the deep fascia.